Spectral Studies of Some Transition Metal Chelates with Thiolactic Anilide and Thiolactic-p-Toluidide, Part-II† - Srivastava, Miru; Kumar, Birendra; Prasad, Ramdeo; Kumari, Nirmala; Nand Prasad, Sachchida (Asian Journal of Chemistry, 2010)
To assign geometrical features to transition and pseudo transition metal(II) complexes with thiolactic anilide (H-TLA) and thiolactic-p-toluidide (H-TLPT), IR spectral studies were carried out. The IR spectra of the Ni(II) and Cu(II) indicate that the metal ions are coordinated through imino nitrogen of the ligand. whereas Co(II). Hg(II). Pb(II) and Ag(I) are coordinated through oxygen of (C=O) group of the ligand. The disappearance of thiol absorption of bond SH stretching vibration reveals that thiol initially deprotonates and then coordinates with metal through S. Electronic spectral studies of transtion metal complexes corroborate with the findings of magnetic studies. i.e., Co(II). Ni(II) and Cu(II) compounds are basically of octahedral geometry.